2014
DOI: 10.7863/ultra.33.6.1065
|View full text |Cite
|
Sign up to set email alerts
|

Reference Charts for Fetal Corpus Callosum Length

Abstract: This work provides new quantile-based reference charts for corpus callosum length measurements that may be useful for diagnosis of congenital corpus callosum anomalies in fetal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…Fetal neurosonography is the method of choice for in-utero brain imaging, and the normal CC and its anomalies are being visualized with increased frequency particularly during the second half of pregnancy [13][14][15][16][17][18]20,29 ; some of these studies include a limited number of fetuses only as early as 16-17 weeks. 13,14 Current understanding is that it is extremely difficult to visualize the CC before 18 weeks of pregnancy mainly due to technical limitations when performing fetal US before this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal neurosonography is the method of choice for in-utero brain imaging, and the normal CC and its anomalies are being visualized with increased frequency particularly during the second half of pregnancy [13][14][15][16][17][18]20,29 ; some of these studies include a limited number of fetuses only as early as 16-17 weeks. 13,14 Current understanding is that it is extremely difficult to visualize the CC before 18 weeks of pregnancy mainly due to technical limitations when performing fetal US before this time.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal ultrasound (US) studies addressed the development of the CC by direct visualization only at a more advanced gestational age, when the CC development has completed [13][14][15][16][17][18] ; but until now US studies analyzing the dynamics of its early development were not possible mainly due to resolution limitations. 19,20 Previously, it was suggested that by using transabdominal US with color Doppler, showing blood flow along the midsagittal image, assuming to represent the pericallosal arteries, can be used as an indirect indication to the presence of some portions of the corpus callosum or as a marker for a CC pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies of the CC included absent, short, thick or apparently normal but stretched CC. The CC was defined as short when length measurement was <3rd centile using reference curves by Cignini et al11 A short CC was then classified as complete (Figure 1) or incomplete (Figure 2); when incomplete, the missing part was noted (rostrum, genu, body, splenium). A CC was defined as thick when ≥3 mm at the mid‐coronal plane as described by Achiron and Achiron 12.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Several different CC nomograms have been presented in the literature. [10][11][12][13][14][15][16][17] The fact that the values presented in these nomograms are very different from each other emphasizes that different regions/populations will have different values. The different results obtained even in studies with similar measurement techniques reveal the necessity for populations to create their own nomograms.…”
Section: ©2020 Perinatal Medicine Foundationmentioning
confidence: 97%
“…[24][25][26] Table 4 shows CC nomograms prepared by different researchers. [10][11][12][13][14][15][16][17] As seen in the table, there are societal differences among such studies ( Table 4). This situation not only reveals the necessity for different populations to develop their own nomograms, but it also requires questioning of the diagnostic accuracy of nomograms.…”
mentioning
confidence: 99%